KONFLIK DALAM ADAPTASI BUDAYA (Studi Deskriptif pada Komunikasi Mahasiswa Fakultas Ilmu Sosial dan Humaniora di Lingkungan UIN Sunan Kalijaga Yogyakarta) - Fajar Iqbal (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
Campus is a miniature community heterogeneity. We can find a diversity of individuals and groups in the dynamics of the campus that are relatively complex. The uniqueness of the campus is also felt by the presence of the academic community are different in purpose and the way to achieve that goal in every interaction between them. Especially for students, this difference can be sourced from a background influenced by family, ethnic, social, and economic before their presence in university life. One campus has a unique advantage which is typical UIN Sunan Kalijaga Yogyakarta. Positioning this campus who use Islam label makes this campus has an environment and atmosphere that is unique compared to other campuses. The research focused on students in the Faculty of Social Sciences and Humanities have found that the students experienced various conflicts in cultural adaptation in the environment UIN Sunan Kalijaga. Starting from intrapersonal conflict to conflict in interpersonal and intergroup dynamics that occur.